Maqashid of Sharia Cooperation - Nurhadi, Nurhadi (Lembaga Yasin AlSys, 2022)
Maqashid The Islamic cooperative is a congregation in a business or community-based business activity. His own philosophy is independence, starting from the self then becoming the independence of the group (people). Or vice versa, group independence that encourages individual independence within it. The resources collected from members are a way to achieve economic sovereignty, so that cooperating is actually a long-term business strategy that secures the business interests of each member from unfair competition. Cooperating is building a fortress from efforts to destroy and colonize large investors and more established business owners. Maqashid The sharia cooperative at the religious level is a concentration of power in driving out the forbidden forms of muamalah and misleading ideologies. Only solidarity that is able to withstand the onslaught of expansion of capitalist business ventures, institutionalized solidarity is called cooperative. Maqashid syirkah sharia cooperatives contain six maqashid: 1). The accumulation of large amounts of capital so that it can be used to hold large jobs; 2). Streamlining macroeconomic rates; 3). The creation of broader and more adequate jobs; 4). The establishment of a sense of brotherhood among fellow capital holders and work partners; 5). The idea of advancing the company is better because it comes from many people too; 6). General transactions can end or cancel.